2010
DOI: 10.2527/jas.2009-2216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the form of dietary fat and the concentration of dietary neutral detergent fiber on ileal and total tract endogenous losses and apparent and true digestibility of fat by growing pigs1

Abstract: An experiment was conducted to determine the effect of the form of dietary fat (extracted or intact fat) and of dietary NDF on ileal and total tract endogenous losses of fat (ELF), on apparent ileal (AID) and apparent total tract digestibility (ATTD) of fat, and on true ileal (TID) and true total tract digestibility (TTTD) of fat in growing pigs. A cornstarch-based basal diet that contained 1.27% fat was prepared and 3 diets were formulated by adding 2.0, 4.0, or 6.0% extracted fat (corn oil) to the basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
106
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 37 publications
31
106
2
Order By: Relevance
“…This response agrees with previous data obtained in pigs (Jørgensen & Fern andez 2000;Kil et al 2010;Leek et al 2004) and poultry (San Juan & Villamide 2000). Greater apparent digestibility of extracted lipid than of intact lipid has also been reported for soybean oil (Agunbiade et al 1992), palm kernel oil (Agunbiade et al 1999) and sunflower oil (San Juan & Villamide 2000).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This response agrees with previous data obtained in pigs (Jørgensen & Fern andez 2000;Kil et al 2010;Leek et al 2004) and poultry (San Juan & Villamide 2000). Greater apparent digestibility of extracted lipid than of intact lipid has also been reported for soybean oil (Agunbiade et al 1992), palm kernel oil (Agunbiade et al 1999) and sunflower oil (San Juan & Villamide 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The improvement in ATTD as dietary lipid concentration increased reflects the fact that the endogenous loss of lipid contributes more to the total output of lipid, and therefore has a greater effect on the apparent digestibility of lipid at lower concentrations of dietary lipid than at higher concentrations (Jørgensen et al 1993;Kil et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AID of EE tended to increase by inclusion of 5% INU or CMC in the diet compared to the control diet, which agree with the observation that increasing dietary fat content increased the AID of fat (Kil et al, 2010). This was probably caused by relatively high proportion of unsaturated fatty acid, which can be absorbed with high efficiency in the small intestine (Dégen et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…This observation agrees with Agyekum et al (2016), who did not find differences in EE digestibility between control diet and a diet containing 300 g kg -1 DDGS. In general, the digestibility of ether extract increases as the oil content in DDGS (Graham et al, 2014b) and the dietary oil content (Kil et al, 2010) increase. Graham et al (2014 a,b) suggested an increase in the EE digestibility of DDGS in relation to corn due to a higher dietary EE content, which did not occur in the present study.…”
Section: Discussionmentioning
confidence: 99%